2019
DOI: 10.1002/jmri.26591
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the time‐length variability of identically protocoled MRI exams

Abstract: Background Clinical variability in MRI exam durations can impede efficient MRI utilization. There is a paucity of data regarding the degree of variability of identically protocoled MRI studies and when nontechnological factors contribute to time‐length variations in MRI exams. Purpose To measure the magnitude of variation in MRI exam duration for identically protocoled MRI exams and to identify potential contributors to variations in MRI exam times. Study Type Retrospective. Subjects 2705 identically protocole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…Avery et al analyzed whether predicting actual examination times is possible [20]. They investigated significant factors influencing the variation of examination duration in an identical MRI examination protocol of the neck.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Avery et al analyzed whether predicting actual examination times is possible [20]. They investigated significant factors influencing the variation of examination duration in an identical MRI examination protocol of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…So könnte z. B. bei den häufig durchgeführten Untersuchungen des Abdomens gemäß der ermittelten Untersuchungsdauern ( Ob eine Vorhersage tatsächlicher Untersuchungszeiten möglich ist, analysierten Avey et al [20]. Sie untersuchten maßgebliche Einflussfaktoren auf die Variation der Untersuchungsdauern bei einem identischen MRT-Untersuchungsprotokoll des Halses.…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Of those studies, transportation time to the CT scanner is the most frequently evaluated. However, in other areas of imaging, factors such as performing technician and hospital setting have been identified as important predictors in imaging time fluctuations 10 . A previous study identified up to 34 unique tasks that are required by a CT technologist to process a patient through a single CT imaging session 11 .…”
mentioning
confidence: 99%
“…However, in other areas of imaging, factors such as performing technician and hospital setting have been identified as important predictors in imaging time fluctuations. 10 A previous study identified up to 34 unique tasks that are required by a CT technologist to process a patient through a single CT imaging session. 11 These tasks include time spent in the electronic medical record, obtaining localization images, contrast administration and recording, interfacing with the CT scanner, reformatting images, sending images to picture archiving and communication system (PACS), stamping the image in PACS, and updating patient location in addition to room related tasks.…”
mentioning
confidence: 99%